School composition, school culture and socioeconomic inequalities in young people's health: Multi‐level analysis of the Health Behaviour in School‐aged Children (HBSC) survey in Wales. (28th February 2017) - Moore, Graham F.; Littlecott, Hannah J.; Evans, Rhiannon; Murphy, Simon; Hewitt, Gillian; Fletcher, Adam
Abstract : Health inequalities emerge during childhood and youth, before widening in adulthood. Theorising, testing and interrupting the mechanisms through which inequalities are perpetuated and sustained is vital. Schools are viewed as settings through which inequality in young people's health may be addressed, but few studies examine the social processes via which institutional structures reproduce or mitigate health inequalities. Informed by Markham and Aveyard's theory of human functioning and school organisation, including their concept of institutional boundaries, critical theories of marketisation and the concept of micro‐political practices within schools, this paper presents analysis of student survey data ( N = 9055) from 82 secondary schools in Wales. It examines the role of socioeconomic composition, social relationships at school and institutional priorities in mitigating or perpetuating health inequality. It finds that affluent schools were most unequal in terms of student health behaviours and subjective wellbeing. In relation to health behaviours, students from affluent families accrue a disproportionate benefit. For wellbeing, students from poorer families reported lower subjective wellbeing where attending more affluent schools. Student–staff relationships appear to be a key mechanism underpinning these effects: poor relationships with staff were predicted by a pupil's position within schools' socioeconomic hierarchy and associated with worse health outcomes. That is, students from the poorest families reported better relationships with teachers where attending less affluent schools. Universal approaches engaging with these social processes are needed to reduce health inequalities.